The Multidivisional Structure as an Enabling Device: A Longitudinal Study Of Discretionary Cash as a Strategic Resource - Russo, Michael V. (Academy of Management Journal, 1991)
This study's argument is that adoption of a multidivisional, or M-form, organizational structure is linked to increases in a firm's levels of discretionary cash. I developed this proposition by assessing the advantages of the M-form as an instrument for directing cash, a fully fungible corporate resource, to alternative uses. Event history analysis was used to model the diffusion of the M-form through a group of electric utilities. Results show that the hypothesized relationship holds, even when the effects of firm size, levels of diversification and vertical integration, and possible imitation effects are controlled.